Correlation between signal transducer and activator of transcription 1 (STAT 1), vascular endothelial growth factor (VEGF), and signal to noise ratio (SNR) value in otoacoustic emission (OAE) examination on organ of Corti cochlea due to cisplatin - Nelfi Disya Amalia Lubis; Hajar Haryuna Tengku Siti; Khalisanni Khalid; Rahadian Zainul (Medicinski glasnik, 2023)
Aim: To assess the cochlear damage caused by cisplatin in the rat cochlea based on decreased signal to noise ratio (SNR) values on otoacoustic emission (OAE) examination and increased expression of signal transducer and activator of transcription 1 (STAT 1) and vascular endothelial growth factor (VEGF) on immunohistochemical examination. Methods: Twenty-four Rattus norvegicus were divided into 4 groups and injected with 8 mg/kgBW of cisplatin intraperitoneally except for control group. The SNR on OAE examination were checked before the treatment and on day 3, 4, and 7 after the treatment. The cochleas were stained immunohistochemically, followed by assessment of the cochlear organ of Corti damage based on STAT 1 and VEGF expression. Results: A decrease in the mean of SNR value was found in accordance with the length of cisplatin exposure. The STAT 1 and VEGF expression increased with duration of cisplatin exposure. A correlation was found between SNR values, STAT 1, and also VEGF expression (p<0.05). Conclusion: An increase of STAT 1 and VEGF expression influences cochlear damage due to cisplatin administration. There was a correlation between STAT 1 and VEGF expression with SNR values in the cochlear organ of Corti of Rattus norvegicus exposed to cisplatin.
Keywords: apoptosis; experimental; immunohistochemistry; rat